Evaluation of the second part of the book (الشيخ معروف النودهى) by Sheikh Mohammed Khal From the perspective of manuscripts and documents - Barzanji, Hemn Mullah Karim; Barzanji, Omar Mullah Karim (Sulaimani Journal for Humanities, 2023)
Sheikh Marfi Nodei Barzanji as a great Kurdish scholar and the Islamic world, mullah, teacher, preacher and chief of the scholars of his time, a Qadiri sheikh under the rule of the Baban ruler, has always been respected His works were the tools of research. Sheikh Mohammed Khal soon realized this and devoted one of his works to researching and proving the biography and works of Sheikh Marfi Nodei However, with the passage of time and the development of publications and communications, new sources and evidence became available, so to evaluate and add new information or reject and correct the errors of the second part of the Sheikh's work Khal is the work of this research, which is based on the comparison of the information in the second part of Sheikh Khal's work with the manuscripts and documents. As a result, some new information was added to Sheikh Khal's work, but much incorrect information was also presented and corrected. Some of the information is the same, only confirmed. Finally, we came to the conclusion that although Sheikh Mohammed Khal is closer to Sheikh Marfi Node in terms of time, but there are many historical facts and documents, not available and the years after Sheikh Khal They have become available, although they existed at that time, so they can enrich and expand the work of Sheikh Khal.
Keywords: Sheikh Marfi Nodei; Barzanj; Barzanji; Sheikh Mohammed Khal; Life and Works